2021
DOI: 10.1186/s12886-021-02061-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural and functional changes in glaucomatous eyes: a multifocal electroretinogram study

Abstract: Background The nasal to temporal amplitudes ratio (N/T) of multifocal electroretinography (mfERG) scans measured within 5° of the macula can be used to detect glaucomatous change. The photopic negative response (PhNR) of mfERG elicited by a circular stimulus centered on the fovea was significantly reduced in eyes with glaucoma. The PhNR to B-wave ratio (PhNR/B) is the optimal measure of the PhNR. However, clinical superiority for evaluating glaucoma patients has not been determined between N/T … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The amplitudes of the first positive peak, P1 and the second positive peak, P2 were studied ( Fig 2A ). The amplitudes of P1 and P2 of the first slice of the second order kernel was measured according to a published method [ 13 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitudes of the first positive peak, P1 and the second positive peak, P2 were studied ( Fig 2A ). The amplitudes of P1 and P2 of the first slice of the second order kernel was measured according to a published method [ 13 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, when a comparison was made between the temporal and nasal hemifields within the central 5° radius, there was a statistically significant difference in the nasal-temporal (N/T) P1 amplitude ratio between normal eyes and glaucoma patients, and there was a significant increase of the P1 amplitude and a nasal-temporal asymmetry was lost in the glaucoma patients [ 12 ] as had been reported [ 13 – 17 ]. Thereafter, significant correlations were found between the ganglion cell complex (GCC) thickness, the mean sensitivities and the N/T P1 amplitude ratio, especially in the inferior and inferotemporal retinal areas (corresponding to superior and superonasal visual field) [ 18 ]. These findings indicated that the mfERGs might be helpful in determining the functional defects in glaucomatous eyes.…”
Section: Introductionmentioning
confidence: 99%